The Secrets of Salt from the Earth’s Core: Bledug Kuwu as an Inspiration for Science Literacy of Elementary School Students - Catur Prasetiawati; Marno Nugroho; Galih Cahya Pratama (Galaxy: Jurnal Pendidikan MIPA dan Teknologi, 2026)
This study aims to analyze the effectiveness of ethnoscience-based Natural Science (IPA) learning by utilizing the Bledug Kuwu phenomenon as a learning resource to enhance elementary school students’ scientific literacy. Bledug Kuwu is a unique geological phenomenon characterized by mud eruptions containing salt, which has long been utilized by the local community as a traditional source of salt. This research employed a mixed-method approach that combined qualitative and quantitative methods. Qualitative data were obtained through field observations, interviews with community members, teachers, and students, as well as an analysis of instructional documents. Quantitative data were collected through scientific literacy tests administered as pre-tests and post-tests to an experimental class and a control class, each consisting of 16 students. Quantitative analysis was conducted using paired sample t-tests, independent sample t-tests, and N-Gain analysis. The qualitative findings indicate that ethnoscience-based science learning incorporating the Bledug Kuwu phenomenon enhances students’ understanding of scientific concepts, curiosity, scientific attitudes, and awareness of environmental and local cultural values. Students demonstrated an improved ability to connect scientific concepts with real-life phenomena in their surrounding environment. The quantitative results show a significant improvement in scientific literacy in the experimental class compared to the control class, as indicated by higher post-test mean scores and moderate-to-high N-Gain values. These findings suggest that integrating local phenomena as ethnoscience-based learning resources makes science learning more contextual, meaningful, and effective. Therefore, Bledug Kuwu has strong potential as an inspiration for science learning to optimally develop scientific literacy and character among elementary school students.